Efektivitas Edukasi Menggunakan Media Whatsapp terhadap Kesiapsiagaan Masyarakat Lombok Barat Menghadapi Bencana Tanah Longsor - Lale Wisnu Andrayani; Cembun Cembun; Hamdan Hariawan (Poltekkes Kemenkes Maluku, 2021)
Landslides as a natural disaster often occur due to the movement of landmasses. Lack of community preparedness in facing disasters is one of the significant risk factors for catastrophe. This study aimed to determine the effectiveness of education using WhatsApp on community preparedness to face landslides. This research is a quasi-experimental study with a pre-post test design with a control group. The number of samples was 30 people taken by simple random and divided into treatment and control groups. The treatment group was given educational intervention with WAG media (WhatsApp Group), while the control group was assigned a P2P (Picture to Picture) intervention. Preparedness data in the form of knowledge and attitudes were analyzed using the Mann-Whitney test. The results showed that statistically, there was no difference in preparedness to face landslides through WAG or P2P. However, there was an increase in readiness through knowledge and attitudes in both groups. Education about landslide preparedness through WAG or P2P has the same effect in increasing public knowledge and perspectives. The information received through WAG or P2P will ultimately influence a person's experience and attitudes regarding landslide disaster preparedness.